2007
DOI: 10.3892/ijo.31.1.5
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference-mediated targeting of urokinase plasminogen activator receptor and matrix metalloproteinase-9 gene expression in the IOMM-lee malignant meningioma cell line inhibits tumor growth, tumor cell invasion and angiogenesis

Abstract: Abstact. Meningiomas are the most commonly occurring tumors of the central nervous system including the brain and spinal cord. Malignant meningiomas are highly aggressive and frequently recur after surgical resection of the tumor. Our previous studies have reported that urokinase plasminogen activator receptor (uPAR) and matrix metalloproteinase-9 (MMP-9) play important roles in tumor progression. In the present study, we have attempted to evaluate the roles of these molecules in the malignant meningioma tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 64 publications
0
19
0
2
Order By: Relevance
“…In addition, we have demonstrated the efficiency of RNAi-mediated targeting of uPAR and MMP-9 in pre-established tumor growth in vivo . We observed a significant regression of pre-established orthotopic tumors upon RNAi-mediated targeting of uPAR and MMP-9 and have also demonstrated that targeting both the proteins simultaneously augmented the therapeutic treatment of human meningiomas (35). …”
Section: Rnai-mediated Strategies For Targeting Mmpsmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, we have demonstrated the efficiency of RNAi-mediated targeting of uPAR and MMP-9 in pre-established tumor growth in vivo . We observed a significant regression of pre-established orthotopic tumors upon RNAi-mediated targeting of uPAR and MMP-9 and have also demonstrated that targeting both the proteins simultaneously augmented the therapeutic treatment of human meningiomas (35). …”
Section: Rnai-mediated Strategies For Targeting Mmpsmentioning
confidence: 72%
“…Small interfering RNAs (siRNAs) are believed to be more potent inhibitors of gene expression with less toxicity (27). Our laboratory had already employed shRNA-based RNAi plasmid system for the downregulation of uPAR in prostate cancer (28), glioma (11, 2933), and meningioma (34, 35). We have utilized a plasmid construct expressing the same small hairpin RNA (shRNA) to target uPAR.…”
Section: Therapeutic Rnai-mediated Strategies For Targeting the Upar mentioning
confidence: 99%
“…Cathepsin B has been implicated in the degradation of the extracellular matrix (ECM) either in secreted form in the extracellular space or attached to the cell surface [10]. In particular, MMP-2 and MMP-9 have been suggested to be associated with prostate cancer metastasis, as high levels of these proteins were measured in plasma and urine in patients with metastatic disease [5], [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…In a study on meningioma, Tummalapalli et al. [33] used the same RNAi preparations as those used by Kunigal et al. to study their effects in the treatment of meningioma that was grown intracranially in nude mice by inoculating IOMM‐Lee cells.…”
Section: Resultsmentioning
confidence: 99%